VD_FINDINFO Plainte / 2021 / 41 vom 23. Dezember 2021 - VD Tribunal cantonal (2021)
ADJUDICATIONVENTE AUX ENCHÈRES, MOINS-VALUE, INDEMNITÉEN GÉNÉRAL, CRÉANCE, ENCHÉRISSEUR | 143 LP, 18 al. 1 LP, 72 al. 1 ORFI